2019
DOI: 10.3389/fgene.2018.00709
|View full text |Cite
|
Sign up to set email alerts
|

Translational Control in Stem Cells

Abstract: Simultaneous measurements of mRNA and protein abundance and turnover in mammalian cells, have revealed that a significant portion of the cellular proteome is controlled by mRNA translation. Recent studies have demonstrated that both embryonic and somatic stem cells are dependent on low translation rates to maintain an undifferentiated state. Conversely, differentiation requires increased protein synthesis and failure to do so prevents differentiation. Notably, the low translation in stem cell populations is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 76 publications
(101 reference statements)
4
71
0
1
Order By: Relevance
“…This breadth was not previously appreciated because prior studies identified DAZL targets in whole testes containing mixed stages of spermatogenesis 15 (Li et al, 2019;Zagore et al, 2018). At the same time, this breadth suggests a role for DAZL in the regulation of global translational levels, which balances stem cell renewal with progenitor formation in other transit-amplifying populations (Blanco et al, 2016;Signer et al, 2014; reviewed in Tahmasebi et al, 2019;Zismanov et al, 2016). Specifically, hematopoietic, hair follicle, and muscle stem cells exhibit lower rates of protein synthesis compared with the 20 progenitor cells to which they give rise (Blanco et al, 2016;Signer et al, 2014;Zismanov et al, 2016), and increased translation promotes the differentiation of stem cells into progenitors (Zismanov et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This breadth was not previously appreciated because prior studies identified DAZL targets in whole testes containing mixed stages of spermatogenesis 15 (Li et al, 2019;Zagore et al, 2018). At the same time, this breadth suggests a role for DAZL in the regulation of global translational levels, which balances stem cell renewal with progenitor formation in other transit-amplifying populations (Blanco et al, 2016;Signer et al, 2014; reviewed in Tahmasebi et al, 2019;Zismanov et al, 2016). Specifically, hematopoietic, hair follicle, and muscle stem cells exhibit lower rates of protein synthesis compared with the 20 progenitor cells to which they give rise (Blanco et al, 2016;Signer et al, 2014;Zismanov et al, 2016), and increased translation promotes the differentiation of stem cells into progenitors (Zismanov et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Somatic stem cells are particularly sensitive to perturbations of protein synthesis and thrive on low translational rates to maintain their undifferentiated state [58,60]. Recent studies showed that specific tRNA modifying enzymes might dynamically affect tRF production across different stem cell compartments and during development [34,41].…”
Section: Trf-mediated Protein Synthesis Control In Skin and Neuronal mentioning
confidence: 99%
“…Interestingly, genes/pathways that are differentially expressed in young versus old renal progenitors include pathways with known effects on organism/stem cells aging (such as TOR) and the translational machinery [81] (Figure 5b). More generally, recent reviews have highlighted that both embryonic and adult stem cells are dependent on low rates of translation to maintain an undifferentiated state [4,82]. Pathways controlling protein synthesis such as the mTOR pathway might then have a crucial role in maintaining renal progenitors in adult cartilaginous fish.…”
Section: The Mtor Signaling Roles During Kidney Repair Disease and Smentioning
confidence: 99%